Implementation of Children's Cognitive Abilities Through Color Recognition Activities in Early Childhood - Annafi’ Nurul ‘Ilmi ‘Azizah; Naila Faizzatis Syifa; Bekti Wulandari; Nurul ‘Aini Muthmainnah; Sulastri; Weipeng Yang (Universitas Islam Zainul Hasan Genggong, 2024)
This study aims to explore and analyze the effectiveness of color recognition activities in enhancing the cognitive abilities of early childhood children at RA Syifaul Qalbi Jumantono. Children are expected to be able to recognize various colors, conduct color mixing experiments, and produce other colors. They should be able to name primary and mixed colors, state the results of color mixing, and recount the color mixing process. The research was conducted using a descriptive qualitative method with classroom action research. Data was collected through observation of children's activities during the sessions, interviews, and documentation. The results indicate that the application of experimental methods in color recognition at RA Syifaul Qalbi Jumantono was successful. The achievements according to the lesson plans and syllabi were acceptable to teachers and students in conducting activities involving color mixing experiments using materials such as bond paper, colored water, and straws. Activities were carried out using planning and implementation systems. This finding emphasizes the significant role of color recognition activities in the cognitive development of early childhood. The practical implication of this research underscores the importance of incorporating color recognition stimulating activities into the early childhood education curriculum to strengthen their cognitive development.